GAMBARAN KADAR HbA1C PADA PASIEN DIABETES MELITUS TIPE 2 DI RSUD WANGAYA - I Gusti Agung Dewi Sarihati; Hurin Nuril Karimah; Nur Habibah (Meditory : The Journal of Medical Laboratory, 2018)
AbstractBackground: Diabetes mellitus (DM) is a degenerative chronic disease and characterized by the increasing of normal blood sugar level which causes high level of glucosuria. The measurement of HbA1c is an accurate way to determine high blood sugar levels over the past two to three months. Objective:The aim of this study was to determine the level of HbA1c in Diabetes mellitus Type 2 patients at the RSUD Wangaya Denpasar City. Methods : This research is a descriptive study and the obtained data will be described using tables and narations. Primary data were obtained by conducting interviews and laboratory examination. The respondents were 30 patients of Diabetes mellitus type 2 who performed HbA1c examination at Wangaya Hospital. Results: The results of this study showed 40% of respondents with HbA1c controlled and 60% uncontrolled. HbA1c controlled with normal BMI 40%, food intake according to recommended 40%, exercising regularly 23.3% regularly consuming antidiabetic drugs 40%. HbA1c is not controlled by a normal BMI 33.3% exercise regularly 3.3% food intake according to the recommended 30%, regular antidiabetic consumption is 40%. Conclusion : From these data it can be concluded that the respondents with controlled HbA1c all had normal BMI, recommended food intake, regularly consumed antidiabetic and most exercise routines.Keywords : HbA1c, Diabetes mellitus Type 2.